Expression and correlation of endoglin, sEndoglin, and MMP-14 on preeclampsia placenta - Febriana Catur Iswanti; Ninik Mudjihartini; Reni Paramita; Yuditiya Purwosunu; Ani Retno Prijanti (Acta Biochimica Indonesiana)
Background: Hypertensive disorders, particularly preeclampsia, are major contributors to maternal mortality and neonatal morbidity. Angiogenic imbalance plays a critical role in placental ischemia, a hallmark of preeclampsia.